2013
DOI: 10.1166/jbn.2013.1563
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Angiogenic and Anti-Cancer Evaluation of Betulin Nanoemulsion in Chicken Chorioallantoic Membrane and Skin Carcinoma in Balb/c Mice

Abstract: Betulin (Bet), the main component of birch tree bark, has been recently reported to exert anticancer activity in several cell lines; however the underlying mechanisms are only partially elucidated. The aims of the present work were to assess the in vivo effects of betulin administered as nanoemulsion (NE) in two experimental models: (i) the chicken embryo chorioallantoic membrane (CAM) assay for the study of anti-angiogenic effects and (ii) the two-stage model of skin carcinoma induced in mice for the study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 35 publications
1
54
1
Order By: Relevance
“…Immunohistochemical staining for smooth muscle actin (SMA) on the specimens treated with betulin in nanoemulsion, next Natural Products and Cancer Drug Discoveryto blank and control samples, are shown in Figure 3. The low expression of the marker in the betulin-treated specimen indicates a minimal implication of pericytes in the angiogenesis process [32]. On the contrary, we found that betulinic acid determined rapid maturation of the vessels and high levels of SMA [31].…”
Section: Tumor Angiogenesis Model On Camcontrasting
confidence: 50%
See 1 more Smart Citation
“…Immunohistochemical staining for smooth muscle actin (SMA) on the specimens treated with betulin in nanoemulsion, next Natural Products and Cancer Drug Discoveryto blank and control samples, are shown in Figure 3. The low expression of the marker in the betulin-treated specimen indicates a minimal implication of pericytes in the angiogenesis process [32]. On the contrary, we found that betulinic acid determined rapid maturation of the vessels and high levels of SMA [31].…”
Section: Tumor Angiogenesis Model On Camcontrasting
confidence: 50%
“…Using the angiogenesis method in the rapid stage of CAM development, we found that pentacyclic triterpenes, betulinic (BA) acid, and betulin (Bet) in various formulations with cyclodextrin and in nanoemulsion are potential antiangiogenic compounds, acting differently, both through direct and indirect mechanisms [31,32]. Immunohistochemical staining for smooth muscle actin (SMA) on the specimens treated with betulin in nanoemulsion, next Natural Products and Cancer Drug Discoveryto blank and control samples, are shown in Figure 3.…”
Section: Tumor Angiogenesis Model On Cammentioning
confidence: 99%
“…Betulinic acid is a pentacyclic triterpene which has the ability to target tumor cells and also vascular endothelial cells, thus functioning as an angiogenesis inhibitor. Dehelean et al recently assessed the in vivo anti-angiogenic and anti-inflammatory effects of betulinic nanoemulsion (8). Based on this work, it was identified that betulinic acid could be formulated in a nanoemulsion delivery system to attain potent anti-inflammatory activity with reduced exposure of the betulinic acid to vital organs.…”
Section: Exploiting Tumor Microenvironmentmentioning
confidence: 99%
“…In recent years, nanoemulsions, a heterogeneous liquid dispersion of nanoscale droplets of one liquid within another, have started evolving as a feasible carrier for the delivery of hydrophobic drugs. Their high solubilization capacity of hydrophobic drugs, ease of production, and long-term stability make nanoemulsions as promising drug delivery systems (2)(3)(4)(5)(6)(7)(8)(9). Nanoemulsion dosage forms have found wide applications in oral drug delivery to enhance the solubility and bioavailability of the hydrophobic drugs (4,10,11).…”
Section: Introduction-applications Of Nanoemulsions In Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation